Influence of Soybean Oil on Binder and Warm Mixture Asphalt Properties - Rezvan Babagoli; Alireza Ameli (Advances in Materials Science and Engineering)
To produce a usual hot mix asphalt, significant amount of energy is used, which causes air pollution. As a result, warm mix asphalt (WMA) is introduced to reduce the mixing and compaction temperature of the mixture. On the one hand, accumulation of waste oil in the ground occupies a large space in the Earth. After the process of frying the oil, if the by-product is not controlled properly, it leads to the pollution of the environment. Hence, utilization of this waste oil can be considered as a sustainable path to dealing with the risk. The main goal of the current research is to evaluate the possibility of exploiting soybean oil to reduce the mixing and compaction temperature of mixtures and produce warm mix asphalt (WMA). Moreover, the rheological and performance properties of mixtures containing soybean are evaluated in this study. The AC-60/70 and 85/100 binders are modified by soybean oil (0%, 1.5%, 2.5%, and 3.5% by weight of binder). Several binder tests are used to measure the physical and rheological behaviors of binders, such as penetration grade, softening point, temperature susceptibility, rotational viscosity (RV), Multiple Stress Creep Recovery (MSCR), and Linear Amplitude Sweep (LAS) tests. Besides, several mixture tests are used to evaluate the performance of the mixture, including four-point bending beam fatigue (FPB), resilient modulus (Mr), indirect tensile strength (ITS), dynamic creep, and wheel track tests. Through MSCR test results, at two stress levels, the Jnr parameter increases as the soybean oil is added to the binder. The results of the LAS test revealed that the fatigue life of binders increases by addition of soybean oil. There is no significant difference between the results of new and waste oil. This in turn makes possible reducing soybean oil production and consumption, and instead frying oil (waste) is reused, which displays no significant difference in terms of chemical and physical properties. Also, the performance test of mixtures indicated that as the soybean oil is added to the mixture, the rutting performance decreases and fatigue performance increases. Based on the results, it is recommended to use 1.5% soybean oil in asphalt mixtures without compromising the performance of the mixture. ANOVA results showed that the warm additive had meaningful effects on MR, ITS, and FE; the same was true for the effects of the warm additive-binder type interaction.